2009
DOI: 10.1007/s10597-009-9255-y
|View full text |Cite
|
Sign up to set email alerts
|

Carrying the Burdens of Poverty, Parenting, and Addiction: Depression Symptoms and Self-Silencing Among Ethnically Diverse Women

Abstract: Depression among women commonly co-occurs with substance abuse. We explore the association between women's depressive symptoms and self-silencing accounting for the effects of known childhood and adult risk indicators. Participants are 233 ethnically diverse, low-income women who abused alcohol/drugs prenatally. Depressive symptomatology was assessed using the Addiction Severity Index. Multivariate logistic regression models examined the association between self-silencing and the dependent depression variable.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…The current study also corroborates the existing literature showing that higher levels of self-silencing and unmitigated communion are significantly related to higher depressive symptoms (Grant et al., 2011; Helgeson, 2003; Helgeson & Fritz, 1999, 2000; Jack, 1999), and it extends those findings to lower quality of life as well as to a sample of predominantly ethnic minority women with and at risk for HIV. Contrary to hypotheses, HIV status did not moderate relationships between higher depressive symptoms, lower quality of life, and traditional gender roles in this sample of women—all of whom originated from high-risk communities characterized by low income, limited educational and work opportunities, homelessness, violence, sexual and physical abuse, and substance abuse.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study also corroborates the existing literature showing that higher levels of self-silencing and unmitigated communion are significantly related to higher depressive symptoms (Grant et al., 2011; Helgeson, 2003; Helgeson & Fritz, 1999, 2000; Jack, 1999), and it extends those findings to lower quality of life as well as to a sample of predominantly ethnic minority women with and at risk for HIV. Contrary to hypotheses, HIV status did not moderate relationships between higher depressive symptoms, lower quality of life, and traditional gender roles in this sample of women—all of whom originated from high-risk communities characterized by low income, limited educational and work opportunities, homelessness, violence, sexual and physical abuse, and substance abuse.…”
Section: Discussionsupporting
confidence: 90%
“…The STSS has been administered to diverse samples domestically and internationally (Drat-Ruszvczak, 2010; Grant et al, 2011; Hautamaäki, 2010; Sikka, Vaden-Goad, & Waldner, 2010; Zoellner & Hedlund, 2010) as well as to a small sample of 15 women with HIV (DeMarco et al, 2001). The α for the total STSS in the current sample was .89, and the four subscale as were .76 (SS), .76 (DS), .49 (CSS), and .83 (EXP).…”
Section: Methodsmentioning
confidence: 99%
“…Silencing the self has been significantly related to higher depressive symptoms among ethnically diverse female populations (Grant, Jack, Fitzpatrick, Jull, & Ernst, 2009; Jack & Ali, 2010; Jack & Dill, 1992). In addition, silencing the self is related to lower levels of income, education, and unemployment for women (Bowleg, Belgrave, & Reisen, 2000; Brody et al, in press; Sen, 2003;Vella, 1994, based on a sample in Australia).…”
Section: Introductionmentioning
confidence: 99%
“…However, African American women are not immune to silencing the self, especially in the context of heterosexual relationships. Ethnic minority women (including African American, Native American, Hispanic, and Asian women) have been found to report similar and even higher levels of silencing the self when compared to White women (Brody et al, in press; Grant, Jack, Fitzpatrick, Jull, & Ernst, 2009). As a group, all women with HIV, regardless of ethnic background, face sexism and may be hindered by gender role prescriptions such as silencing the self.…”
Section: Introductionmentioning
confidence: 99%
“…However, no racial/ethnic differences were found among participant groups and findings were reported only for the total group. More recently, Grant, Jack, Fitzpatrick, and Ernst (2011) found that self-silencing was significantly associated with depression among a racially/ethnically diverse sample of women who reported heavy alcohol or illicit drug use during pregnancy. Harrington, Crowther, and Shipherd (2010) found a significant correlation between self-silencing, exposure to trauma that resulted in distress, internalization of strong Black woman ideology, and difficulty inhibiting or regulating emotions.…”
Section: Self-silencingmentioning
confidence: 99%